CITRAAN LIMA PUISI RITUS KONAWE KARYA IWAN KONAWE - Nuryadin Nuryadin (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This research uses Structural approach. With this structural approach, the researcher can see the extent to which a literary work has a moral value in the novel to be analyzed. The source of data in this research is Konawe's ritual poem by Iwan Konawe and its contents. The form of data in the form of elements of images in five poems contained in each of five poems by Iwan Konawe. The research process is done by data collection and data analysis. Data obtained by way of reading and recording. The analysis is presented in the description. The result of this research is submitted as a whole that Iwan Konawe poem image, is a poem image contained in five poems Konawe ritus Iwan Konawe work can be used as learning and inspiration in real life. Keywords: image of five poems in the Konawe Rite.